(untitled) (International Journal of Engineering and Computer Science, 2014)
Android is a software stack for mobile devices that includes an operating system, middleware and key applications. The android provides the tools and APIs necessary to begin developing applications on the Android platform using programming language. Android is a widely anticipated open source operating system for mobile devices that provides a base operating system, an application middleware layer, a Java software development kit (SDK), and a collection of system applications. Android has a unique security model, which focuses on putting the user in control of the device. Android devices however, don’t all come from one place, the open nature of the platform allows for proprietary extensions and changes. Our operational semantics provide some necessary foundations to help both users and developers of Android applications deal with their security concerns. One way to provide security in android OS is that we can have the multiuser security system. As android is open source operating system we can download the source and modify accordingly. To add this feature in android we can develop an application of multiuser and the security can be implemented on android operating system. To implement this facility we are going to make an android application which supports multiple users. After developing this application we can put it in android OS externally or inbuilt as per user requirements. After putting this application in smart phone we can make more than one users. And this will provide more security to your smart phone. Also provide more security to smart phone we can have location tracking system called as LBS i.e. Location Based Technology. This technology will enables to track the location of unauthorized users. If any unauthorized user enters wrong password more than five times then his photo will be captures(if front camera available) and location will be tracked also location information will be send on registered admin’s email-id.